2018
DOI: 10.1002/cbdv.201700565
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Essential Oil Composition and Antioxidant Activity in Perovskia abrotanoides Kar. Collected from Different Regions in Iran

Abstract: Essential oil (EO) composition, phenolic content, and antioxidant activity were investigated in 17 P. abrotanoides populations collected from different geographical regions in Iran. The highest (3.61%) and lowest (1.25%) essential oil yields were measured in populations from Semnan Province (PSESM ) and PISKS from Isfahan Province, respectively. GC/MS analysis identified camphor (4.05 - 35.94%), 1,8-cineole (7.15 - 24.34%), borneol (0 - 21.75%), and α-pinene (2.05 - 10.33%) as the main constituents of Perovski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The higher content of NDF in Cichorium intybus L. can be attributed to the lower leaf to stem ratio. Part of the high levels of fat in Perovskia abrotanoides Kar and Teucrium polium L. can be attributed to the high amounts of essential oils that have been previously reported by researchers (Ghaffari et al 2018 ; Mahmoudi and Nosratpour 2013 ). The forage digestibility and DMI in ruminants are influenced mainly by the dietary NDF (Harper and McNeill 2015 ).…”
Section: Discussionmentioning
confidence: 67%
“…The higher content of NDF in Cichorium intybus L. can be attributed to the lower leaf to stem ratio. Part of the high levels of fat in Perovskia abrotanoides Kar and Teucrium polium L. can be attributed to the high amounts of essential oils that have been previously reported by researchers (Ghaffari et al 2018 ; Mahmoudi and Nosratpour 2013 ). The forage digestibility and DMI in ruminants are influenced mainly by the dietary NDF (Harper and McNeill 2015 ).…”
Section: Discussionmentioning
confidence: 67%
“…These monoterpenes are inverse to (E)-caryophyllene, α-humulene, and allo-aromadendrene in winter. This negative relationship between monoterpenes and sesquiterpenes can be interpreted as competition between two pathways for the same precursor (Ghaffari et al, 2018;Ghaffari et al, 2019). Thus, we can suggest that isopentenyl pyrophosphate fluxes are dominant to the plastid (site of monoterpene synthesis) under winter conditions, whereas this flux tends toward the cytosol (site of sesquiterpene synthesis) in summer (McCaskill & Croteau, 1994).…”
Section: Resultsmentioning
confidence: 94%
“…[147], Perovskia abrotanoides Kar. [148], Thymus vulgaris L. [149], Rosmarinus officinalis L. [150] and Salvia officinalis L. [151]. Recent studies have demonstrated the various effects of borneol in the treatment of chronic and neuropathic pain through activation of the GABAergic system and blocking transient receptor potential ankyrin 1 in the spinal cord [152,153].…”
Section: Borneolmentioning
confidence: 99%